2022
DOI: 10.3389/fmed.2022.842423
|View full text |Cite
|
Sign up to set email alerts
|

Daily Step Counts in Patients With Chronic Kidney Disease: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: BackgroundPhysical inactivity is an essential factor in the prognosis of patients with chronic kidney disease (CKD). Daily step count is a straightforward measure to assess physical activity levels. Understanding the step counts among different CKD stages is essential to change sedentary behavior.ObjectivesThis systematic review and meta-analysis aimed to investigate the daily step counts in patients with CKD at a different stage.DesignA systematic review and meta-analysis.Data SourcesThe literature search was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…The incorporation of physical activity monitoring into clinical care has the potential to improve outcomes (12,13), but it requires consistent use of a monitoring device by patients over a long time period. However, the majority of studies quantifying activity levels in patients receiving hemodialysis have been short term, in the order of 1–2 weeks or less (6). Many used pedometers, which assess uniaxial motion of the hip (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of physical activity monitoring into clinical care has the potential to improve outcomes (12,13), but it requires consistent use of a monitoring device by patients over a long time period. However, the majority of studies quantifying activity levels in patients receiving hemodialysis have been short term, in the order of 1–2 weeks or less (6). Many used pedometers, which assess uniaxial motion of the hip (6).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing adoption of wearable technologies provides a unique opportunity to understand activity patterns and their relation to clinical outcomes. Prior studies in the hemodialysis population have used wearable devices to examine physical activity levels (6), but only one has attempted long-term use (7), and few have utilized the detailed data that such devices provide (8,9). We hypothesized that highly granular data collection coupled with patient-centered outcomes measures would yield new insights into patterns of behavior and activity among patients receiving hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…This evolution, intermittent and in general unpredictable, may evolve to ESRD, driving the patients to a worsening of quality of life and posing a burden on the health service and the environment [ 34 , 35 , 36 ]. The traditional control of risk factors and the improvement of the patient’s lifestyle, tackling sedentariness for several protective benefits derived from physical activity [ 13 , 15 , 19 ], is a recommended action [ 17 , 18 , 35 ]. Moreover, in the presence of PAD where mobility is restricted and the option of revascularization may increase the risk of progressive renal dysfunction [ 6 , 7 ], rehabilitative exercise may represent the necessary tool.…”
Section: Discussionmentioning
confidence: 99%
“…As a further critical issue for PAD-CKD patients, the restricted mobility due to vascular disease and the progressive sedentariness associated with CKD severity [ 13 ] deprive patients of the protective effects related to physical activity [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most other evidence on wearable devices in patients with ESKD centres around the use of wearables for monitoring physical activity. In a systematic review, the mean step count was 4111 in patients on haemodialysis and 4264 in patients on peritoneal dialysis, clearly below the daily recommended target [ 42 ]. Reduced physical activity is related to mortality in this population [ 43 ], and recent studies have shown that a home-based exercise program is not only feasible [ 44 ] but also beneficial [ 45 ].…”
Section: Wearable Devices For Diagnosis and Monitoring In Ckdmentioning
confidence: 99%